The Northern Norway mother-and-child contaminant cohort study: implementation, population characteristics and summary of dietary findings - Veyhe, Anna Sofia; Hansen, Solrunn; Sandanger, Torkjel Manning; Nieboer, Evert; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2012)
Objectives. To describe the essential features of a new Northern Norway mother-and-child contaminant cohort study called MISA, including its rationale, content, implementation and selected findings (mostly dietary). Study design. Cross-sectional with longitudinal aspects. Methods. Five hundred and fifteen eligible women were enrolled in early pregnancy, with 391 completing the study protocol that included a self-administrated food frequency questionnaire (FFQ) and donation of biological samples for contaminant analysis in the 2nd trimester, just after delivery, and 6 weeks postpartum. Macronutrient consumption was converted to energy intake, and the amounts of both macro- and micronutrients ingested were estimated. Some of the MISA findings were compared to data available in the Medical Birth Registry of Norway (MBRN). Results. Compared to all 2004–2006 mothers in Northern Norway, the study cohort women were about 2 years older and smoked less; on average, they had close to 16 years of education. Parity, gestational age and birth weight of the newborn were comparable as well. The estimated average dietary intake of 8.1 MJ per day was less than that recommended by the Nordic Nutritional Recommendations (NNR), but the intake of micronutrients per MJ complied. Conclusions. Although the final cohort sample size was less than targeted, the generally good comparisons observed between MBRN-registered information for the study cohort and dropouts suggest that this occurrence introduced minimal bias. The agreement of the observed demographic and clinical characteristics of the cohort women and newborns with all births in Northern Norway implied acceptable external validity. Also, the dietary findings aligned well with Norwegian national data and guidelines and other studies, as did the high prevalence of breastfeeding. The MISA database is considered suitable for exploring associations between contaminant exposure and diet, enhancing our knowledge of the interplay of the physiological changes that occur in mothers with ...